Analyzing Spiritual Well-Being of Senior High School Learners: Basis for Intervention Program - Mercado, Matias; Galgo, Kathlene Jane; Acedillo, John Leonard; Aleonar, Maryl Justine; Bigwas, Samantha (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the spiritual well-being of 220 Senior High School learners at Holy Cross of Mintal, Inc. (HCMI) to provide a diagnostic basis for a targeted intervention program. Anchored in Erikson’s Psychosocial Theory and the Holistic Theory of Wellness, the research employed a descriptive-predictive design using an adapted 30-item "Tradition-Specific Measures of Spiritual Well-Being" instrument (alpha = 0.97). Results indicated an overall Very High level of spiritual well-being (M = 4.28, SD = 0.63). Stepwise discriminant analysis revealed that Relationship with God and Service with God are the most significant predictors distinguishing high-perceiving learners from others, while general "Service" was found to be a common trait across all groups. These findings suggest that depth of personal connection, rather than mere religious activity, is the primary driver of spiritual health. The study proposes the VINE Project as a dynamically responsive intervention to strengthen these predictive dimensions.